2015
DOI: 10.11604/pamj.2015.20.407.6010
|View full text |Cite
|
Sign up to set email alerts
|

Does intranasal fentanyl provide efficient analgesia for renal colic in adults?

Abstract: IntroductionIntranasal fentanyl provides rapid and powerful analgesia which is particularly interesting in patients without intravenous access. We propose to use it for analgesia in adults presenting renal colics.MethodsA prospective study was conducted from the 2nd January to February 2013 in our emergency department. Patients aged up to 18 years old who presented with renal colic were included in this audit. Patients were excluded if they had loss of consciousness, cognitive impairment, acute or chronic nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
4
0
5
Order By: Relevance
“…Out of 23 studies included, 18 studies were conducted in children: 1 PS in the PHES (Murphy et al, 2017 [ 38 ]), 9 observational studies (Akinsola et al, 2018 [ 39 ], Anderson et al, 2022 [ 40 ], Cole et al, 2009 [ 41 ], Crelin et al, 2010 [ 42 ], Finn et al, 2010 [ 43 ], Kelly et al, 2018 [ 44 ], Nemeth et al, 2019 [ 45 ], Saunders et al, 2010 [ 46 ], Schaefer et al, 2015 [ 47 ]) and 8 RCTs (Borland et al, 2011 [ 48 ], Fein et al, 2017 [ 49 ], Frey et al, 2019 [ 50 ], Graudins et al, 2015 [ 51 ], Quinn et al, 2021 [ 52 ], Reynolds et al, 2017 [ 53 ], Ruffin et al, 2022 [ 54 ], Younge et al, 1999 [ 30 ]) in the ED; 5 studies were conducted in the adult population: 1 observational study in the PHES setting (Tanguay et al, 2020 [ 55 ]), 2 observational studies (Assad et al, 2023 [ 56 ], Belkouch et al, 2015 [ 57 ]) and 2 RCTs (Nasr Isfahani et al, 2022 [ 58 ], Nazemian et al, 2020 [ 59 ]) in the ED setting; one subgroup analysis of an observational study reported data on the elderly patients in the PHES (Tanguay et al, 2020 [ 55 ]). A total of 10,280 patients were included: 1203 in the PHES setting (94 children, 729 adults and 380 elderly) and 9077 in the ED setting (8714 children and 363 adults).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 23 studies included, 18 studies were conducted in children: 1 PS in the PHES (Murphy et al, 2017 [ 38 ]), 9 observational studies (Akinsola et al, 2018 [ 39 ], Anderson et al, 2022 [ 40 ], Cole et al, 2009 [ 41 ], Crelin et al, 2010 [ 42 ], Finn et al, 2010 [ 43 ], Kelly et al, 2018 [ 44 ], Nemeth et al, 2019 [ 45 ], Saunders et al, 2010 [ 46 ], Schaefer et al, 2015 [ 47 ]) and 8 RCTs (Borland et al, 2011 [ 48 ], Fein et al, 2017 [ 49 ], Frey et al, 2019 [ 50 ], Graudins et al, 2015 [ 51 ], Quinn et al, 2021 [ 52 ], Reynolds et al, 2017 [ 53 ], Ruffin et al, 2022 [ 54 ], Younge et al, 1999 [ 30 ]) in the ED; 5 studies were conducted in the adult population: 1 observational study in the PHES setting (Tanguay et al, 2020 [ 55 ]), 2 observational studies (Assad et al, 2023 [ 56 ], Belkouch et al, 2015 [ 57 ]) and 2 RCTs (Nasr Isfahani et al, 2022 [ 58 ], Nazemian et al, 2020 [ 59 ]) in the ED setting; one subgroup analysis of an observational study reported data on the elderly patients in the PHES (Tanguay et al, 2020 [ 55 ]). A total of 10,280 patients were included: 1203 in the PHES setting (94 children, 729 adults and 380 elderly) and 9077 in the ED setting (8714 children and 363 adults).…”
Section: Resultsmentioning
confidence: 99%
“…One PS reported that INF effectively reduced pain at each time point after administration (5, 30, 45 and 60 min) [ 57 ]; one RS reported no difference in pain reduction with IV morphine [ 56 ]; one RCT reported a reduced efficacy at 5 min and 10 min compared with IN ketamine, with no difference at 30 and 40 min [ 58 ]; one RCT reported a reduced efficacy of INF compared with IV fentanyl at each time point after administration [ 59 ]. Regarding secondary efficacy outcomes, one RS reported no difference in time to first analgesic administration between INF and IV morphine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a proposal would lead us to suggest that the specific regulatory process (i.e., enhanced error feedback/cognitive conflict) evoked with transcranial stimulation may have biased the participants in favor of more conservative values and beliefs. Indeed, recent studies in political psychology have begun to document the differential regulatory mechanisms underlying right- and left-wing ideology (Janoff-Bulman et al, 2008 , 2009 ; Janoff-Bulman, 2009 ), with recent fMRI investigations demonstrating a specific relationship between multi-dimensional scales of conservatism and activity of the right DLPFC (e.g., Zamboni et al, 2009 ). Zamboni and colleagues further discuss these findings in terms of a heightened sense of cognitive dissonance between self-interest and fairness that results in more complex social judgments in Conservative individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha comparado la utilización de fentanilo intravenosa con intranasal para manejo del dolor posoperatorio al igual que en el manejo analgésico de pacientes pediátricos quemados, fractura de huesos largos, y se determinó que la administración intranasal fue rápida y además sin eventos adversos significativos [31], [32]- [36].…”
Section: Fentanilounclassified